2011
DOI: 10.1097/ncn.0b013e3181fcbe3d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ICU Nurses' Use of the Clinical Information System in Taiwan

Abstract: With the fast development of computer software and hardware, technology application is ubiquitous, and many healthcare services have integrated a clinical information system into daily practice. With today's information technology, everyone should possess basic computer competency to meet on-the-job demands and especially to use an information system in healthcare. Thus, the purpose of this study was to explore Taiwanese nurses' computer competency, the interface usability, and any change in the nurses' practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Recently, authors in Ta iwan examined nurses' use of EHRs [13], although specific findings about eMAR use were not outlined. Beauscart-Zephir and colleagues [14] found that communication among physicians and nurses in French hospitals was impacted when computerized physician order entry (CPOE) was installed.…”
Section: Emars and Patient Safetymentioning
confidence: 99%
“…Recently, authors in Ta iwan examined nurses' use of EHRs [13], although specific findings about eMAR use were not outlined. Beauscart-Zephir and colleagues [14] found that communication among physicians and nurses in French hospitals was impacted when computerized physician order entry (CPOE) was installed.…”
Section: Emars and Patient Safetymentioning
confidence: 99%
“…15,23 Furthermore, understandable and easily labeled and marked time frame boxes or grids are required on the recording instrument for data collection, and time intervals as the observed activities should usually take 2 to 15 minutes. 17,22 Activities are classified based on research purposes, and most would divide nursing activities into five categories: direct care, indirect care, documentation, unit-related activity, and personal activity. [13][14][15]17,23 To understand the work of nurses and properly record their observed activities on the instrument, each observer must have clinical knowledge, such as a senior nurse with nursing experience 13 or a trained medical student 14 or senior nursing students.…”
Section: Work Sampling Methodsmentioning
confidence: 99%
“…17,22 Activities are classified based on research purposes, and most would divide nursing activities into five categories: direct care, indirect care, documentation, unit-related activity, and personal activity. [13][14][15]17,23 To understand the work of nurses and properly record their observed activities on the instrument, each observer must have clinical knowledge, such as a senior nurse with nursing experience 13 or a trained medical student 14 or senior nursing students. 15 For limiting the interrater reliability, related training and tests must be given to each observer, including the data collection format, coding, description, and guidance.…”
Section: Work Sampling Methodsmentioning
confidence: 99%
See 2 more Smart Citations